Diplatin, a Novel and Low-Toxicity Anti-Lung Cancer Platinum Complex, Activation of Cell Death in Tumors via a ROS/JNK/p53-Dependent Pathway, and a Low Rate of Acquired Treatment Resistance - Lin, Xixi; Jia, Yongliang; Dong, Xinwei; Shen, Jian; Jin, Yachao; Li, Yanyou; Wang, Fang; Anenberg, Eitan; Zhou, Jiancang; Zhu, Jianping; Chen, Xiaoping; Xie, Qiangmin; et al. (Frontiers in Pharmacology, 2019)
BACKGROUND: Platinum based drugs prevail in the treatment of lung cancer due to their relative effectiveness despite known side effects such as neurotoxicity. There is a need for testing of new compounds for improved effectiveness and safety profiles in order to develop new treatments for clinical practice. OBJECTIVES: A novel water soluble platinum complex-diplatin was synthesized, its anti-tumor potency and toxicology profile were evaluated in both murine models of xenograft tumors and lung cancer cell lines. METHODS: The effects of diplatin, cisplatin (DDP) and carboplatin (CBP) on the viability of 9 lung tumor cell lines and one normal human lung epithelial cell line were evaluated using MTT assay. Therapeutic index (TI) was calculated as LD50/ED50 to identify and compare the ideal therapeutic window of the above compounds. Diplatin anti-tumor effects were assessed in lung xenograft tumors of nude mice; molecular mechanisms of therapeutic effects were also elucidated. RESULTS: Diplatin had desirable IC50 compared to CBP in a variety of cultured tumor cells notably lung tumor cells. In the mouse xenograft lung tumor diplatin led to a substantially improved therapeutic index when compared to the effects of DDP and CBP. Importantly, diplatin could inhibit the growth of DDP resistant lung tumor cells. Diplatin’s mode of action was cell cycle arrest in the G2/M phase and induction of lung tumor apoptosis via ROS/JNK/p53-mediated pathways. CONCLUSION: Diplatin was observed to have anti-tumor effects in mice with both greater potency and safety. These observations indicate that diplatin is a promising candidate compound for clinical applications.